Recent Progress in High‐Performance Lithium Sulfur Batteries: The Emerging Strategies for Advanced Separators/Electrolytes Based on Nanomaterials and Corresponding Interfaces. Issue 19 (19th August 2021) - Wang, Xiaoxiao; Deng, Nanping; Wei, Liying; Yang, Qi; Xiang, Hengying; Wang, Meng; Cheng, Bowen; Kang, Weimin
Abstract: Lithium‐sulfur (Li−S) batteries, possessing excellent theoretical capacities, low cost and nontoxicity, are one of the most promising energy storage battery systems. However, poor conductivity of elemental S and the "shuttle effect" of lithium polysulfides hinder the commercialization of Li−S batteries. These problems are closely related to the interface problems between the cathodes, separators/electrolytes and anodes. The review focuses on interface issues for advanced separators/electrolytes based on nanomaterials in Li−S batteries. In the liquid electrolyte systems, electrolytes/separators and electrodes system can be decorated by nano materials coating for separators and electrospinning nanofiber separators. And, interface of anodes and electrolytes/separators can be modified by nano surface coating, nano composite metal lithium and lithium nano alloy, while the interface between cathodes and electrolytes/separators is designed by nano metal sulfide, nanocarbon‐based and other nano materials. In all solid‐state electrolyte systems, the focus is to increase the ionic conductivity of the solid electrolytes and reduce the resistance in the cathode/polymer electrolyte and Li/electrolyte interfaces through using nanomaterials. The basic mechanism of these interface problems and the corresponding electrochemical performance are discussed. Based on the most critical factors of the interfaces, we provide some insights on nanomaterials in high‐performance liquid or state Li−S batteries in the future. Abstract : The interface problems for advanced separators/electrolytes based on nanomaterials.